1992
DOI: 10.1148/radiology.183.2.1561358
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal bleeding: treatment with gastrointestinal arterial embolization.

Abstract: Retrospective analysis of 36 embolization procedures in 29 patients with gastrointestinal bleeding was undertaken, and the presence or absence of coagulopathy was identified as a major factor affecting embolization outcome. Embolization was successful in 18 of 29 (62%) patients and unsuccessful in 11 (38%). Eight of 11 failures (73%) occurred in patients with a coagulopathy, whereas three patients (27%) in whom embolization was successful also had a coagulopathy. Embolization was 2.9 times more likely to be un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(76 citation statements)
references
References 0 publications
1
73
0
2
Order By: Relevance
“…Cancer-related bleeding seems to be much more difficult to control than other causes of bleeding, not only because of direct cancer invasion into adjacent vascular structures, but also because of severe mucositis caused by chemotherapy or radiation that can induce vascular erosion or tissue necrosis [25][26][27]. Several previous studies have analyzed the factors affecting clinical outcome after TAE using various embolic materials for gastrointestinal tract bleeding, and the results suggested that a high bleeding tendency was associated with a higher risk of early bleeding recurrence [28][29][30]. However, in our present study, a high bleeding tendency did not significantly decrease the clinical success rate of TAE.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer-related bleeding seems to be much more difficult to control than other causes of bleeding, not only because of direct cancer invasion into adjacent vascular structures, but also because of severe mucositis caused by chemotherapy or radiation that can induce vascular erosion or tissue necrosis [25][26][27]. Several previous studies have analyzed the factors affecting clinical outcome after TAE using various embolic materials for gastrointestinal tract bleeding, and the results suggested that a high bleeding tendency was associated with a higher risk of early bleeding recurrence [28][29][30]. However, in our present study, a high bleeding tendency did not significantly decrease the clinical success rate of TAE.…”
Section: Discussionmentioning
confidence: 99%
“…Acute surgical intervention will eventually be required in 10%-15% of patients, 7 but is associated with a mortality of 25%. 8 Mesenteric angiography and angioembolization is a well described diagnostic and therapeutic option in the management of both acute UGIB [9][10][11][12] and LGIB [13][14][15][16] after endoscopic failure. The decision to perform mesenteric angiography or proceed directly with surgical intervention is often at the discretion of the attending surgeon.…”
mentioning
confidence: 99%
“…High technical and clinical success rates of endovascular treatments for GI bleeding have been reported [7][8][9][10][11][12]. TAE is generally regarded as a safe procedure with few complications.…”
Section: Discussionmentioning
confidence: 99%